Cost study of dynamically transparent networks - DOYLE, LINDA; O'MAHONY, DONAL EDWARD (Optical Society of America, 2008)
The network equipment cost benefit of dynamic wavelength routing is compared with point-to-point IP networks and static wavelength routing in a simple ring topology with variable network traffic loading.
PUBLISHED
San Diego, USA
Keywords: dynamic wavelenght routing